Hubungan Work Life Balance Dengan Kinerja Perawat Di Instalasi Rawat Inap Rumah Sakit Ibnu Sina YW-UMI Kota Makassar - Riani Nur Afiah Namudat; Wardiah Hamzah; Nurul Hikmah (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Nurses play a crucial role in hospital services, making optimal performance essential for healthcare quality. An imbalance between work and personal life (work-life balance) may negatively affect nurses’ performance. This study aimed to analyze the relationship between work-life balance and nurse performance in the inpatient unit of Ibnu Sina YW-UMI Hospital, Makassar.This study employed a quantitative, cross-sectional design. A total of 53 nurses were selected using cluster purposive sampling. The independent variable was work-life balance, which included three dimensions: time balance, involvement balance, and satisfaction balance. The dependent variable was nurse performance. Data were collected using a structured questionnaire and analyzed using the chi-square test at the 0.05 significance level. The results showed that most nurses had good work-life balance and performance. Bivariate analysis indicated a significant relationship between all dimensions of work-life balance (time, involvement, and satisfaction) and nurse performance (p-value = 0.000). Nurses with better work-life balance tended to perform better than those with poorer balance. In conclusion, work-life balance is significantly associated with nurse performance. Therefore, hospitals should pay greater attention to maintaining nurses’ work-life balance by optimizing workload management and work schedules to improve overall performance.